1985
DOI: 10.1002/j.1875-9114.1985.tb03405.x
|View full text |Cite
|
Sign up to set email alerts
|

Glipizide: A Second‐generation Sulfonylurea Hypoglycemic Agent; Pharmacology, Pharmacokinetics and Clinical Use

Abstract: Glipizide is a second-generation sulfonylurea in which the substitutions on the arylsulfonylurea nucleus are large, relatively nonpolar groups. This chemical change increases the intrinsic hypoglycemic activity of the molecule 100-fold on a weight basis compared to first-generation agents. In addition, the pharmacokinetic properties, spectrum and severity of side effects and metabolism of this agent are somewhat different from those of first-generation sulfonylureas. The most important component of the antidia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 35 publications
(17 reference statements)
1
13
0
Order By: Relevance
“…Overall, these results are in agreement with previous results where glibenclamide and the first generation sulfonylurea tolbutamide reverted the antinociception produced by diclofenac, but not by indomethacin (Ortiz et al, 2003;Ortiz, 2011). In the present study, we demonstrated for the first time that the antinociceptive effects of diclofenac were blocked by glipizide, a second generation sulfonylurea (Lebovitz, 1985). It is one of the most regularly prescribed drugs for the treatment of patients with noninsulin-dependent diabetes (Wysowski et al, 2003).…”
Section: Effect Of Sulfonylureas On the Antinociceptive Effects Of DIsupporting
confidence: 95%
“…Overall, these results are in agreement with previous results where glibenclamide and the first generation sulfonylurea tolbutamide reverted the antinociception produced by diclofenac, but not by indomethacin (Ortiz et al, 2003;Ortiz, 2011). In the present study, we demonstrated for the first time that the antinociceptive effects of diclofenac were blocked by glipizide, a second generation sulfonylurea (Lebovitz, 1985). It is one of the most regularly prescribed drugs for the treatment of patients with noninsulin-dependent diabetes (Wysowski et al, 2003).…”
Section: Effect Of Sulfonylureas On the Antinociceptive Effects Of DIsupporting
confidence: 95%
“…Glipizide is a second-generation sulfonylurea used in the treatment of Type II diabetes [1000]. First-pass metabolism of glipizide appears to be minimal, and the absolute oral bioavailability of the drug is reported to be 80-100% [1000].…”
Section: Glipizidementioning
confidence: 99%
“…Even though a majority of patients show an initial 'response', in most studies, only about 50% demonstrate a clinically meaningful lowering of plasma glucose (for example, fasting glucose concentration below 7.8 mmol/L; Lebovitz 1985).…”
Section: Discussionmentioning
confidence: 99%